Development of an immunochromatographic strip incorporating anti‐mitragynine monoclonal antibody conjugated to colloidal gold for kratom alkaloids detection. Issue 7 (30th January 2018) - Limsuwanchote, Supattra; Putalun, Waraporn; Tanaka, Hiroyuki; Morimoto, Satoshi; Keawpradub, Niwat; Wungsintaweekul, Juraithip
Abstract: A lateral flow‐based immunochromatographic strip was developed for the rapid detection of mitragynine (MG), a dominant alkaloid found in the leaves of kratom. Monoclonal antibody (mAb) against MG (anti‐MG mAb) was conjugated to colloidal gold and used as a recognition probe. MG‐ovalbumin conjugate (MG‐OVA) and goat anti‐mouse IgG were immobilized on the strip to produce a test zone and control zone, respectively. Based on the principle of a competitive assay, MG in a test sample competed with MG‐OVA resident in the test zone to bind with colloidal gold‐anti‐MG mAb, resulting in an inverse relation of color intensity at the test zone and MG amount. The limit of detection (LOD) of the immunochromatographic strip is determined at 1 mg/mL of MG by visual assessment and 0.60 mg/mL by Image J analysis. The developed immunochromatographic strip can determine MG in kratom cocktails and kratom leaf samples. It could serve as a rapid and simple diagnostic kit for the detection of MG in kratom samples. Abstract : The immunochromatographic strip was developed using anti‐mitragynine monoclonal antibody labelled with colloidal gold nanoparticles as a detection probe. It was applied to determine kratom alkaloids in kratom leaves and kratom cocktails.